Analysis on the optimal location of distributed generation in power system network - Arbaiyah binti Hasanuddin (2023)
Distributed Generation (DG) is place in distribution system to do the main responsibility in the suburhan business and also industrial sectors in power system nestwork. DistributedGeneration (DG) offer an option to the conventional type of source of electricity i.e. oil, gas, coal, water ect. and the current electrical system also can also be enhanced.